KHUTTAH `ILAJIYYAH `ALA ASÂS NAZARIYYAH TAHLÎL AL-AKHTÂ‘ AL-LUGAWIYYAH FÎ TA`LÎM AL-LUGAH AL-`ARABIYYAH - Afandi, Ahmad; Saputra, Edy; Fadhlan, Muhammad (Universitas Islam Negeri Mataram, 2022)
The field of Arabic language education suffers from shortcomings in the adopted curriculum. Learners realize serious problems when learning Arabic in the classroom. The teacher is committed to solving their problems and makes a conscious effort to improve the educational content in the classroom. The theory of linguistic errors analysis plays an important role in identifying learners' learning problems and taking the necessary educational measures to overcome them. The study of linguistic errors makes a good contribution - theoretically - about the common linguistic characteristics in the teaching of the second language. In practice, the teacher assists in designing remedial courses by following the steps of analyzing language errors in extracting them. It complies with providing the appropriate material that prevents learners from repeating their linguistic error.